Food Access Patterns and Barriers among Midlife and Older Adults with Mobility Disabilities - Deborah L. Huang; Dori E. Rosenberg; Shannon D. Simonovich; Basia Belza (Journal of Aging Research, 2012)
We examined where midlife and older adults with a mobility disability accessed food outside the home in King County, Washington, USA, how they travelled to these food destinations, and facilitators and barriers to food access using qualitative interviews. Thirty-five adults aged ≥50 years with a mobility disability (defined as use of an assistive device for mobility) were interviewed. Supplemental objective information was obtained from a Global Positioning System device worn by participants for 3 days. Participants primarily accessed food at grocery stores, restaurants, and coffee shops/cafés. The most common transportation modes were walking, obtaining a ride from friends, motorized chair/scooter, and public transit. Location and proximity of food destinations were factors affecting participants’ ability to access these destinations. Adequate space, ease of entry, available amenities such as restrooms, and helpful people were facilitators for participants to access food outside the home.